Adenosine deaminase and guanosine deaminase activities in sera of patients with viral hepatitis - Kalkan, A; Bulut, V; Erel, O; Avci, S; Bingol, NK (Fundaco Oswaldo Cruz, 1999)
In order to investigate purin and primidin metabolism pathways in hepatitis, adenosine deaminase (ADA) and guanosine deaminase (GDA) activities in sera of patients with different types and manifestations of viral hepatitis disease (A, B, C, D, E, chronic, acute) were investigated and compared with the control group of healthy individuals. Hepatitis cases were classified with respect to their serological findings and clinics. When compared all the hepatitis cases with the controls, levels of aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase enzymes, as well as ADA and GDA, were significantly higher than rite control group (p<0.01). Levels of ADA and GDA in hepatitis cases were determined as 26.07+/-11.98 IU/l and 2.37+/-1.91 IU/l, respectively. When compared their ADA and GDA levels amongst the classified hepatitis groups, there was no difference in ADA levels amongst cases (p>0.05). However; GDA levels in hepatitis A group were closed to the controls. Increase in serum ADA activities in hepatitis forms may be dependent or? and reflect the increase in phagocytic activity of macrophages and maturation of T-lymphocytes, and may be valuable in monitoring in vii-al hepatitis cases.
Keywords: adenosine deaminase; guanosine deaminase; viral hepatitis